2016
DOI: 10.1097/hjh.0000000000001090
|View full text |Cite
|
Sign up to set email alerts
|

Creatine kinase inhibition lowers systemic arterial blood pressure in spontaneously hypertensive rats

Abstract: To our knowledge, this is the first report on the BP-lowering effect of creatine kinase inhibition. Our data indicate that modulation of the creatine kinase system is a potential novel treatment target for hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
46
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(51 citation statements)
references
References 42 publications
4
46
0
Order By: Relevance
“…High CK might lead to greater ATP buffer capacity for renal sodium retention regardless of ancestry or ethnicity . The findings of this study add to the body of evidence indicating that CK enhances ATP buffer capacity near ATPases, resulting in higher blood pressure . We previously showed that human vascular contractility is CK‐dependent and that CK expression in resistance arteries has a near‐perfect correlation with blood pressure .…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…High CK might lead to greater ATP buffer capacity for renal sodium retention regardless of ancestry or ethnicity . The findings of this study add to the body of evidence indicating that CK enhances ATP buffer capacity near ATPases, resulting in higher blood pressure . We previously showed that human vascular contractility is CK‐dependent and that CK expression in resistance arteries has a near‐perfect correlation with blood pressure .…”
Section: Discussionsupporting
confidence: 55%
“…High skeletal muscle CK activity is associated with a predominance of “fast” type II fibers, lower oxidative capacity, and capillary rarefaction, which may contribute to increased peripheral resistance and blood pressure . Thus, the aggregated evidence indicates that high CK activity may enhance ATP buffer capacity in different tissues and facilitate the development of hypertension . In line with this, high resting plasma CK correlates with failure of antihypertensive therapy and treatment with an oral systemic CK inhibitor reduces blood pressure in spontaneously hypertensive rats, with evidence of attenuated vascular contractility and sodium retention …”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Animal and human studies found that plasma and tissue CK activity was a main determinant of blood pressure and of resistance artery contractility, while hypertension was found to be more severe in individuals with high plasma CK activity . In addition, the creatine analogue and competitive CK inhibitor GPA safely and reversibly reduced blood pressure in spontaneously hypertensive rats . Therefore, the CK enzyme system is a potential target for lowering blood pressure in humans with high plasma CK activity.…”
Section: Discussionmentioning
confidence: 99%
“…The blood pressure was measured using an indirect blood pressure meter (Softron Biotechnology, Beijing, China). During the measurement of the blood pressure, we tried to minimalize stress for the animals (Karamat et al, 2016).…”
Section: Grouping and Experimental Protocolmentioning
confidence: 99%